Hotspots and future trends of autophagy in Traditional Chinese Medicine: A Bibliometric analysis - Jun Zhao; Guang-wei Liu; Cheng Tao (Heliyon, 2023)
Objective: To discuss the hotspots and future trends of autophagy in traditional Chinese medicine (TCM) and provide a reference for researchers in this field. Method: Using visual analysis tools, metrological statistics and visual research on the pertinent literature in the area of autophagy use in TCM were undertaken in the core collection database of the Web of Science. By examining the authors, keywords, research circumstances, research hotspots, and trends of linked research, the use of autophagy in TCM was investigated. Results and Conclusions: A total of 916 studies were included, among which Beijing University Chinese Medicine was the largest number of advantageous research institutions, followed by Shanghai University Traditional Chinese Medicine and Guangzhou University Chinese Medicine.The keywords of literature research primarily comprise apoptosis, activation, inhibition, pathway, mechanism, oxidative stress, proliferation, NF-κB, cancer, mtor, etc. At present, the research on autophagy in the field of TCM is increasing on a year-to-year basis. The research has focused on the role played by TCM in malignant tumors, atherosclerosis, Alzheimer's disease through autophagy, and the regulation of autophagy signaling pathways (e.g., PI3K/AKT/mTOR signaling pathway, TLR4 signaling pathway,nrf2 signaling pathway and NF-κB signaling pathway). In the future, the therapeutic effect of TCM on chemotherapy-resistant tumor cells through autophagy pathway, the role of TCM mediating mitophagy and activating autophagy function, and the therapeutic effect of TCM components represented by luteolin on tumors, asthma, myocardial injury and other diseases through autophagy mechanism will be the research hotspots in the future.